2014
DOI: 10.3892/mmr.2014.2438
|View full text |Cite
|
Sign up to set email alerts
|

Raltitrexed induces mitochondrial-mediated apoptosis in SGC7901 human gastric cancer cells

Abstract: Abstract. Raltitrexed is a specific inhibitor of thymidylate synthase (TS), which has been considered as a potential chemotherapeutic agent for the treatment of advanced gastric cancer. In the present study, the apoptosis mechanisms of raltitrexed in SGC7901 human gastric cancer cells were investigated. The cytotoxic activity of raltitrexed on SGC7901 cells was determined by cell counting kit-8 (CCK-8) assay. The CCK-8 assay indicated that raltitrexed inhibits SGC7901 cell growth in a dose-and time-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Previous studies have indicated that evodiamine may stimulate the production of ROS to induce apoptosis by causing mitochondrial damage (27,28). The present study found that following treatment with evodiamine, the anti-apoptotic genes Survivin and Bcl-2 in the mitochondria-associated apoptosis pathway were significantly downregulated, while the downstream caspase-3 and caspase-8 activity was significantly upregulated, indicating that the mitochondrial pathway is important for evodiamine-induced apoptosis.…”
Section: B Asupporting
confidence: 55%
“…Previous studies have indicated that evodiamine may stimulate the production of ROS to induce apoptosis by causing mitochondrial damage (27,28). The present study found that following treatment with evodiamine, the anti-apoptotic genes Survivin and Bcl-2 in the mitochondria-associated apoptosis pathway were significantly downregulated, while the downstream caspase-3 and caspase-8 activity was significantly upregulated, indicating that the mitochondrial pathway is important for evodiamine-induced apoptosis.…”
Section: B Asupporting
confidence: 55%
“…The first-line drugs used in TACE include fluorouracil (5-FU), doxorubicin (DOX), and oxaliplatin (OXA), and are associated with a number of adverse effects, indicating a need for an alternative agent [5]. Raltitrexed (also known as tomudex) is a quinazoline antifolate thymidylate synthase inhibitor [6] that has been shown to have anticancer effects in both preclinical and clinical studies [7][8][9][10]. Reports have shown its efficacy and safety in many tumor types including colorectal and breast cancers; however, the clinical data of raltitrexed in HCC treatment are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been shown to induce apoptosis and is suggested to be central to the apoptotic pathway (23,24). As a group of proteolytic enzymes at the end of the apoptotic signaling pathway, the caspase family plays an essential role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%